Melhorias da atenção e modulação autonômica cardíaca após um programa de treinamento intervalado com esforços supra máximos de duas semanas: uma abordagem de fidelidade - Sousa, Arilson Fernandes Mendonça de (2018)
Only two weeks of sprint interval training (SIT) has been shown to be associated with positive changes in aerobic capacity and cardiac autonomic control. Both aerobic capacity and autonomic control have been shown to be positively associated with improved attention. However, to date, the relationship between this type of training and attention has not been investigated yet. The aim of the present study was to investigate the influence of two weeks of SIT on aerobic capacity, cardiac autonomic control and attention components in healthy university students; Also, to verify if the training fidelity would influence these adaptations. One hundred and nine participants were divided into experimental (EG) and control (CG) groups. EG performed a SIT program consisting of 6 sessions of maximal 4 × 30 s all-out efforts on a cycle ergometer, interspersed with active 4-minute rests. The criterion for fidelity was to reach> 90% of the estimated maximum heart rate (HR) during sprint sessions. After analysis, EG was divided into fidelity groups HIGH (n = 26) and LOW (n = 46), respectively. The attention components were evaluated through the Attention Network Test (ANT). The aerobic capacity (VO2max) was estimated according to Astrand's nomogram while the sum of the skinfolds: pectoral, triceps, subscapular, medial axillary, abdomen, suprailiac and thigh was verified. Autonomic HR control was assessed by HR variability (HRV) and HR complexity at rest and during ANT, before and after six sessions of SIT. Both HIGH and LOW significantly increased aerobic capacity, vagal modulation before and during ANT and executive control, and decreased body fat after SIT (p <0.05). However, only HIGH participants showed an increase in HR complexity and accuracy in ANT responses when compared to LOW (p <0.05). Two weeks of SIT improved executive control, body fat, aerobic capacity and autonomic control in university students, with better results reported for the HIGH group.